STRATEGIC TRANSFORMATION OF JAPANESE AUTOMAKERS IN INDONESIA UNDER CHINESE EV MARKET PRESSURE - Ria Andriani; Vina Islami; Heirunissa Heirunissa; Otto Siregar (Jurnal Comparative: Ekonomi dan Bisnis, 2026)
This study examines the strategic transformation of Japanese automakers in Indonesia in sustaining market dominance amid the rapid rise of Chinese electric vehicle (EV) manufacturers. For decades, Japanese brands have controlled Indonesia’s automotive market through strong brand equity, extensive distribution networks, localized production, and high consumer trust. However, the aggressive expansion of Chinese EV producers, characterized by competitive pricing, technological innovation, and rapid product diversification, has begun to disrupt the traditional competitive landscape. This research aims to analyze the extent of this competitive threat and its implications for market dynamics. Using a descriptive quantitative approach based on sales data and market share analysis, the findings indicate that while Japanese automakers remain dominant, their position is increasingly challenged by accelerating EV adoption. Analytical frameworks including Product Life Cycle (PLC), Competitive Dynamics, SWOT, and TOWS reveal that conventional vehicles are in maturity and moving toward decline, whereas Chinese EVs are in a rapid growth phase, threatening Japanese ICE dominance. The study concludes that sustaining leadership requires accelerated EV innovation, cost efficiency, strategic partnerships, and organizational agility. However, this study is limited by reliance on secondary data and lack of firm-level insights. Future research should incorporate longitudinal and primary data-approaches.